Predictors of Village Government Financial Decision Making in Bantul Regency - M.Acc, Zulfatun Ruscitasari S.E.; Subroto, Melvin Rahma Sayuga; Herlinawati, Erica (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2023)
The SDGs program of the village becomes sustainable development to be achieved by looking at the predictors of decision-making in the village. This research aims to look at the phenomenon that exists in managing village funds in making a report so that it affects decision-making. The methodology uses SEM-PLS using PLS Smart Software 4.0 to simultaneously evaluate mediation effects. The questionnaires were distributed and processed to obtain data from 97 respondents in Bantul, Yogyakarta. Testing more accurately the factors that influence decision-making with creative accounting practices, the authors add several factors such as ethical values, future orientation, government governance, effectiveness and quality of financial reporting are mutually influential.